Diimide-mediated hydrogenation of nitrile butadiene rubber - Amira Shafiqa Salleh Huddin,; Goh, Yi-Fan; Naharullah Jamaluddin,; Siti Fairus Mohd Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The hydrogenation of nitrile butadiene rubber (NBR) has shown great potential for improving its physical, thermal, mechanical, and chemical stability. Hydrogenation process of NBR in this work involved the utilization of diimide produced from the interaction between hydrazine hydrate (N2H4) and hydrogen peroxide (H2O2), with the addition of boric acid as a promoter. Attenuated total reflectance Fourier transform infrared (ATR-FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and X-ray diffraction (XRD) were used to evaluate the degree of hydrogenation, glass transition, thermal stability, and rubber crystallinity, respectively. The highest hydrogenation degree was 99%, which resulted in a 57% gel content. Upon hydrogenation, both the glass transition temperature (Tg) and decomposition temperature (Td) increased. The hydrogenated rubber samples generally showed an amorphous state, except for the 99% hydrogenated sample, which displayed a semi-crystalline state. However, using diimide for direct hydrogenation yields a side reaction from the free radicals in the system, which leads to gel formation. Optimization was accomplished by employing the response surface methodology (RSM), which entailed manipulating parameters such as the total solid content (TSC) of NBR, reaction time, and the mole ratio of H2O2 to N2H4, to reduce the percentage of gel content. The RSM analysis identified the optimum reaction conditions as a 1:1 mole ratio of H2O2: N2H4 and 25% TSC, with a reaction time of 8 h, which yielded 32% gel content percentage, where a mole ratio of H2O2 to N2H4 and reaction time indicated a synergistic effect, whereas TSC denoted an antagonistic effect.